Inclusão de crianças autistas: um estudo sobre concepções e interações no contexto escolar - Lemos, Emellyne Lima de Medeiros Dias Lemos (2012)
The autism spectrum involves deviations in development since the early years of life in areas of social interaction, communication and imagination. Numerous researches are performed and many aspects remain inconclusive, especially regarding to the etiology, treatment possibilities and integration in regular schools. Considering the importance of social interaction in children's development and the influence of parent´s and professionals concepts about inclusive practices, the present study aims to analyze the social interactions between children with autism and other children in the context of regular schools in João Pessoa, Brazil, considering the mediation of teachers, parents and their conceptions about the child and school inclusion. A group of 42 children and four teachers from two regular private schools, as well as four children diagnosed with autism spectrum between 3 and 5 years of age and their parents. To collect the data, semi-structured interviews recorded, through a mini tape recorder, were used. Also, two videotapes of 20 minutes were made at each of the situations of courtyard and classrooms, of which 10 minutes were transcribed and analyzed. With the objective to characterize the children in this study we used the CARS rating scale. Regarding data analysis, interviews were transcribed and analyzed using the technique of content analysis. The recordings were transcribed and analyzed using behavioral categories of teachers and children with autism described in qualitative terms, from case studies, and quantitative, from the frequencies. The results show that parents are satisfied with the educational inclusion held with their children. These parents point positive characteristics of their children, while identifying the difficulties inherent in autism. As for the teachers observed those are reformulating their conceptions of the possibilities of these children and understand inclusion as a practice that goes beyond the inclusion in school. In relation to the behaviors in both the classroom and in the courtyard there was a higher frequency in the use of directives and physical support. With regard to the autistic child there was a greater frequency of behaviors to look at people, led initiative to action, appropriate response and smile revealing the participation of autistic children in interactional terms. Considering that the behaviors of these children can be influenced by the interactive contexts, the mediation of adult and, especially, the particularities of each child this study aims to support guidelines for parents and professionals mainly regarding the inclusion of autistic children in regular schools.